Penerapan Model Pembelajaran Scientific Inquiry Berbasis Budaya Melayu untuk Meningkatkan Hasil Belajar Mahasiswa - Harahap, Saima Putrini R; Umi Kalsum, Syarifah (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2024)
The problem found in learning is low student learning outcomes. The research aims to determine the effect of a scientific learning model based on Malay culture on improving student learning outcomes. In this research, researchers used a quantitative approach. The sample used was 55 third semester students consisting of 2 classes. Class A is an experimental class with 27 students. Class B is a control class with 28 students. This research was carried out in the Hydrology Course. The data collection technique used is a test. The data analysis technique uses the help of IBM SPSS Statistics 23, namely the normality test, homogeneity test and Independent Sample t-test with a significance level of 5% or 0.05. Based on the research results, the average pretest score for the experimental class was 35.41 and the control class was 35.14. Then given different treatment, the experimental class was taught with a scientific learning model based on Malay culture and the control class with conventional learning. After learning was completed, the average post-test score for the experimental class was 74.85 and the control class was 63.14. After carrying out the Independent Sample t-test, a significant value of 0.000 <0.05 was obtained, so it can be concluded that the scientific learning model based on Malay culture has an effect on improving student learning outcomes.